Crossing the Bridge From Degeneration to Deformity: When Does Sagittal Correction Impact Outcomes in Adult Spinal Deformity Surgery?. Issue 3 (1st February 2023) - Williamson, Tyler K.; Krol, Oscar; Tretiakov, Peter; Joujon-Roche, Rachel; Imbo, Bailey; Ahmad, Salman; Owusu-Sarpong, Stephane; Lebovic, Jordan; Ihejirika-Lomedico, Rivka; Dinizo, Michael; Vira, Shaleen; Dhillon, Ekamjeet; et al.
Abstract : Background: Patients with less severe adult spinal deformity (ASD) undergo surgical correction and often achieve good clinical outcomes. However, it is not well understood how much clinical improvement is due to sagittal correction rather than treatment of the spondylotic process. Purpose: Determine baseline thresholds in radiographic parameters that, when exceeded, may result in substantive clinical improvement from surgical correction. Study Design: Retrospective. Materials and Methods: ASD patients with BL and two-year data were included. Parameters assessed: sagittal vertical axis, pelvic incidence–lumbar lordosis mismatch, pelvic tilt, T1 pelvic angle, L1 pelvic angle, L4–S1 lordosis, C2–C7 sagittal vertical axis, C2–T3, C2 slope. Outcomes: Good Outcome (GO) at two years: [meeting either: (1) Substantial Clinical Benefit for Oswestry Disability Index (change >18.8), or (2) Oswestry Disability Index <15 and Scoliosis Research Society Total>4.5]. Binary logistic regression assessed each parameter to determine if correction was more likely needed to achieve GO. Conditional inference tree run machine learning analysis generated baseline thresholds for each parameter, above which, correction was necessary to achieve GO. Results: We included 431 ASD patients. There were 223 (50%) that achieved a GO by two years. Binary logistic regression analysis demonstrated, with increasing baseline severity in deformity, sagittal correction was more often seen in those achieving GO for each parameter(all P <0.001). Of patients with baseline T1 pelvic angle above the threshold, 95% required correction to meet GO (95% vs. 54%, P <0.001). A baseline pelvic incidence–lumbar lordosis >10° (74% of patients meeting GO) needed correction to achieve GO (odds ratio: 2.6, 95% confidence interval: 1.4–4.8). A baseline C2 slope >15° also necessitated correction to obtain clinical success (odds ratio: 7.7, 95% confidence interval: 3.7–15.7). Conclusions: Our study highlighted point may be present at which sagittal correction has an outsized influence on clinical improvement, reflecting the line where deformity becomes a significant contributor to disability. These new thresholds give us insight into which patients may be more suitable for sagittal correction, as opposed to intervention for the spondylotic process only, leading to a more efficient utility of surgical intervention for ASD.